2006
DOI: 10.1177/14690446060070050801
|View full text |Cite
|
Sign up to set email alerts
|

Infection control link professionals' knowledge of Clostridium difficile

Abstract: lostridium difficile is a common cause of diarrhoea in hospitalised patients. It can result in longer hospital stays and due to the need for strict isolation procedures can add significantly to nursing workload. Additionally, it can be very distressing for the patient and if patients are vulnerable to infection it can have serious health consequences. Cross-transmission can be limited by good infection prevention and control practices, however this relies on a sound knowledge base and support from the infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For safe disposal of waste and linen and caring for patients with MRSA or C. difficile, findings suggest that poor knowledge led to poor application of practice. This finding is supported by similar studies which found that healthcare workers were not aware of basic infection prevention measures required to care for patients with MRSA (Trim et al, 2003;Marshall et al, 2004;Easton et al, 2007;Lugg and Ahmed, 2008) or C. difficile (Vaughan et al, 2006), and suggests that this has not changed with time and a raising awareness strategy within the NHS.…”
Section: Discussionmentioning
confidence: 68%
“…For safe disposal of waste and linen and caring for patients with MRSA or C. difficile, findings suggest that poor knowledge led to poor application of practice. This finding is supported by similar studies which found that healthcare workers were not aware of basic infection prevention measures required to care for patients with MRSA (Trim et al, 2003;Marshall et al, 2004;Easton et al, 2007;Lugg and Ahmed, 2008) or C. difficile (Vaughan et al, 2006), and suggests that this has not changed with time and a raising awareness strategy within the NHS.…”
Section: Discussionmentioning
confidence: 68%
“…Such training provided for cannulation may not include local policies, products and care plans, while the training for catheterisation does, suggesting a need to improve training surrounding cannulation. This finding is echoed in the literature surrounding infection prevention knowledge, application and compliance, which has identified a need for increased infection prevention education (Stein et al, 2003;Trigg et al, 2008;Wu et al, 2006), improvements to current infection prevention education (Mann and Wood, 2006;Vaughan et al, 2006) and the causes for current limited knowledge to be established (Trim et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Saving Lives (DH, 2010) also advocates that NHS organisations should provide annual training on the prevention and control of infection in general to all staff. However previous studies have found that no research recommends the most effective way to deliver generic infection prevention and control education (Mann and Wood, 2006; Vaughan et al, 2006). Furthermore current training tends to be formal, short and taught didactically by content experts, for large groups of eclectic healthcare workers in the hope that enhanced knowledge will persuade staff to improve their compliance in relation to clinical care (Cole, 2008).…”
Section: Introductionmentioning
confidence: 99%